Factors influencing the decision to hire contract labour by Indian manufacturing firms. (2nd October 2019) - Singh, Jaivir; Das, Deb Kusum; Abhishek, Kumar; Kukreja, Prateek
ABSTRACT: Over a third of workers employed in the Indian formal manufacturing sector are 'contract' workers – hired through the services of labour contractors, facing lower wages and no job security in relation to regular workers. We investigate the role of a variety of factors that influence the decision of employers to hire in contract workers, using information from a specially commissioned survey of manufacturing firms. While there are immediate cost advantages that tilt firms towards hiring in contract labour, a counterforce has employers favouring regular workers in firms that have a large proportion of their workforce concentrating on production activity – probably instances where long-term human capital investment by regular workers is important for the firm. Abbreviation : CLA: Contract Labour (Regulation and Abolition) Act, 1970 ASI: Annual Survey of Industries NIC: National Industrial Classification MSME: Micro, Small and Medium Enterprises SEZ: Special Economic Zone ICRIER: Indian Council for Research on International Economic Relations